Increasing of Blood-Brain Tumor Barrier Permeability through Transcellular and Paracellular Pathways by Microbubble-Enhanced Diagnostic Ultrasound in a C6 Glioma Model - Zhang, Jinlong; Liu, Heng; Du, Xuesong; Guo, Yu; Chen, Xiao; Wang, Shunan; Fang, Jingqin; Cao, Peng; Zhang, Bo; Liu, Zheng; Zhang, Weiguo (Frontiers in Neuroscience, 2017)
Most of the anticancer agents cannot be efficiently delivered into the brain tumor because of the existence of blood-brain tumor barrier (BTB). The objective of this study was to explore the effect of microbubble-enhanced diagnostic ultrasound (MEUS) on the BTB permeability and the possible mechanism. Glioma-bearing rats were randomized into three groups as follows: the microbubble-enhanced continued diagnostic ultrasound (MECUS) group; the microbubble-enhanced intermittent diagnostic ultrasound (MEIUS) group and the control group. The gliomas were insonicated through the skull with a diagnostic ultrasound and injected with microbubbles through the tail veins. Evans Blue (EB) and dynamic contrast-enhanced-MRI were used to test changes in the BTB permeability. Confocal laser scanning microscopy was used to observe the deposition of the EB in the tumor tissues. The distribution and expression of junctional adhesion molecule-A (JAM-A) and calcium-activated potassium channels (KCa channels) were detected by a Western blot, qRT-PCR, and immunohistochemical staining. In the MEUS groups, the EB extravasation (11.0 ± 2.2 μg/g in MECUS group and 17.9 ± 2.3 μg/g in MEIUS group) exhibited a significant increase compared with the control group (5.3 ± 0.9 μg/g). The MEIUS group had more EB extravasation than the MECUS group. The Ktrans value of the dynamic contrast-enhanced-MRI in the MEUS groups was higher than that of the control group and correlated strongly with the EB extravasation in the tumor (R2 = 0.97). This showed that the Ktrans value might be a non-invasive method to evaluate the BTB permeability in rat glioma after microbubble-enhanced ultrasound treatment.Western blot, qRT-PCR and immunohistochemical staining revealed that MEUS increased the KCa channels expression and reduced JAM-A expression in glioma. This change was more obvious in the MEIUS group than in the MECUS group. The results demonstrated that MEUS effectively increased the BTB permeability in glioma. The mechanisms might involve the up-regulation of KCa channels expression and affecting the formation of tight junctions in the BTB by a reduction of JAM-A expression. These findings might provide some new guidance for glioma drug therapy.